Super-sampling with a reservoir - Paige, B; Sejdinovic, D; Wood, F (AUAI Press, 2016)
We introduce an alternative to reservoir sampling, a classic and popular algorithm for drawing a fixed-size subsample from streaming data in a single pass. Rather than draw a random sample, our approach performs an online optimization which aims to select the subset that provides the best overall approximation to the full data set, as judged using a kernel two-sample test. This produces subsets which minimize the worst-case relative error when computing expectations of functions in a specified function class, using just the samples from the subset. Kernel functions are approximated using random Fourier features, and the subset of samples itself is stored in a random projection tree. The resulting algorithm runs in a single pass through the whole data set, and has a per-iteration computational complexity logarithmic in the size of the subset. These “supersamples” subsampled from the full data provide a concise summary, as demonstrated empirically on mixture models and the MNIST dataset.